Preliminary Study: Instrumentation Design for Studying Granular Segregation. (August 2019) - Munir, Rahmawati; Rahmayanti, Handika Dany; Yuliza, Elfi; Amalia, Nadya; Utami, Fisca Dian; Viridi, Sparisoma; Abdullah, Mikrajuddin
Abstract: Rice winnowing is a process of separation of small and large rice grains by air flow practiced by farmes. This process shows interesting phenomenon but has never been documented by previous researchers. Based on the movements performed within rice winnowing, we tried to design a simulation instrument that resembled rice winnowing process. This research aims to investigate the process of granulars segregation with different size or density. We also observed carefully using manually released objects were captured for 60 seconds by digital camera (Nikon L840, 16 megapixel and 30 fps) in a video mode. Every video tracked using video tracker then analyzing the results. Furthermore, the results of study can be useful to develop a model of granulars segregation based on size or density.